DESAIN E-WORKBOOK MATA KULIAH VOKASI TEKNIK PENGEMBANGAN PRODUK KULIT MENGGUNAKAN POSITIVE REINFORCEMENT DAN DUAL CODING - Ulfah Nafi'ah; Anwar Hidayat; Mochammad Charis Hidayahtullah; Galuh Puspita Sari; Yuafni; Reinny Devi Febriyanti Razak (LPPM Universitas Abdurrab, 2026)
This study aims to design a multimedia-based e-workbook using positive reinforcement and dual coding approaches to support the learning process of the Product Development Techniques for Leather course at Politeknik ATK Yogyakarta. The research employed the Design Thinking method, consisting of five stages: empathize, define, ideate, prototype, and test. Data were collected through focus group discussions (FGD) with course instructors and interviews with students to identify user needs. The final product is an interactive e-workbook that combines text and visuals simultaneously (dual coding) and incorporates motivational elements such as encouraging phrases, constructive instructions, and visually engaging layouts (positive reinforcement). Multimedia features such as Augmented Reality (AR), QR codes, and visually structured layouts were integrated to enrich the learning experience. Evaluation results from subject matter experts and students yielded an average score of 4.37 (on a 5-point Likert scale), indicating that the media is highly feasible and effective in supporting vocational learning.